Theological knowledge internalization in man and sin doctrine learning - Eirene Mary; Samuel Udau; I Putu Ayub Darmawan (International Journal of Humanities and Innovation (IJHI), 2022)
The learning pattern of the Dogmatics course tends to be directed at mastering and memorizing Christian doctrines, and participants find it difficult to connect Christian doctrines learned to real-life realities. The course materials become things to memorize, not things to believe. In the Dogmatics learning process, a learning pattern that can improve understanding of course materials and be applied in everyday life is needed. This research aims to describe the application of the combined teaching method to improve participants' understanding of course materials and to be able to relate them to daily life. It is descriptive &qualitative research. The research was conducted at Simpson Theological Seminary Ungaran on the odd semester of 2020/2021 Academic Year. The objects of this research were 15 participants and lecturers of Christian Religious Education major participating in the Dogmatics I course. The results show that applying a combination of lecture and Q&A methods could improve participants' understanding of course material and connect lecture material to daily life. Evaluation of learning outcomes showed a good level of understanding of the course material, in which participants could connect the concepts in learning to everyday life